Sommes-nous [réellement] envahis par les anglicismes ? Deux décennies d’anglicismes - Léopold Julia (Lengas, 2022)
The ideological struggle against Anglicisms is a good illustration of unilingualism as defined by Henri Boyer: "no competition (for the national language), no deviance (from the norm)". The term invasion also raises two aspects: the increase in numbers and the threat of replacement. By lexicographical then sociolinguistic analysis of anglicisms among the new words in dictionaries (1998-2022), we will show how this threat is quite relative.